2020
DOI: 10.1002/ente.202000061
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin‐Based Conducting Polymer Hydrogel for Supercapacitor Application

Abstract: Herein, the electrochemical properties and energy storage capability of a flexible, all‐solid‐state supercapacitor based on the supramolecular assembly of polypyrrole (PPy) and the anion of 5,10,15,20‐tetrakis(4‐sulfonatophenyl)‐21H,23H‐porphine manganese(III) chloride (MnTSPP) are reported. The electrode material consists of a conductive polymer hydrogel formed through the gelation initiated by cross‐linking of the dopant MnTSPP anion in the PPy chains. The morphology of the cross‐linked polymer hydrogel is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…[22,23] Instead, strategies to enhance the physico-electrochemical properties of CPHs have mostly focused on in-situ polymerization of the conducting polymer in a nonconducting hydrogel matrix, [24][25][26] or in the presence of crosslinkers. [7,27,28] Such approaches incorporate insulating components that can diminish electrical transport properties. Conjugated polyelectrolytes are defined by a structure containing a π-conjugated backbone bearing pendant ionic groups.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] Instead, strategies to enhance the physico-electrochemical properties of CPHs have mostly focused on in-situ polymerization of the conducting polymer in a nonconducting hydrogel matrix, [24][25][26] or in the presence of crosslinkers. [7,27,28] Such approaches incorporate insulating components that can diminish electrical transport properties. Conjugated polyelectrolytes are defined by a structure containing a π-conjugated backbone bearing pendant ionic groups.…”
Section: Introductionmentioning
confidence: 99%
“…The anion of MnTSPP enhanced the charge storage capability by facilitating electron transfer between the polymer interchains. 109 Very recently, Mei et al 110 reported porphyrin-based conjugated microporous polymers (CMP) as electrode material for designing flexible SCs. A series of porphyrinbased CMPs (MTAPP-CMP, M = Cu and H2) were synthesized by polycondensation of metal porphyrins and pyromellitic dianhydride which were then hybridized with carbon nanotubes (CNTs) to form flexible MTAPP-CMP/CNTs.…”
Section: Porphyrinoids For Electrochemical Capacitorsmentioning
confidence: 99%
“…Among numerous possibilities, nanostructured materials exhibiting supramolecular interactions are best suited for overcoming these challenges [53,55,56] . These can be employed as either electrode materials or electrolytes in SC/battery systems [54,57–59] . Electrolytes capable of showing supramolecular interactions are not just beneficial for rendering potentiality to be used as solid electrolytes (gel polymer electrolytes).…”
Section: Introductionmentioning
confidence: 99%
“…[53,55,56] These can be employed as either electrode materials or electrolytes in SC/battery systems. [54,[57][58][59] Electrolytes capable of showing supramolecular interactions are not just beneficial for rendering potentiality to be used as solid electrolytes (gel polymer electrolytes). Rather, they are effective in providing improved ion conductivity in both interface and bulk regions, which is a daunting challenge for solid-state SC systems.…”
Section: Introductionmentioning
confidence: 99%